Influence of Blade Profiles on Plastic Centrifugal Pump Performance. (22nd December 2020) - Zhang, Hui; Tang, Lingfeng; Zhao, Yongtao
Abstract : To study the influence of blade profiles of the plastic centrifugal pump on pump performance, the impeller blade profiles were designed and drawn by the single arc method, double arc method, logarithmic spiral method, and B-spline curve method, respectively, with the known structural parameters.The shape and size of four profiles were drawn, and two-dimensional models and three-dimensional models of four impellers and volute were completed, respectively. The impeller models were printed by 3D printing technology, and the performance experiments of the plastic centrifugal pump were carried out. The numerical simulation of the internal flow field was performed. From the contours of the velocity and pressure, the vapor volume fraction distribution, and fluid-structure interaction analysis of impellers, the impeller drawn by the logarithmic spiral method was better than others. The optimization of the logarithmic spiral method was completed. The impeller inlet and outlet diameters ( D 1 and D 2 ) and impeller inlet and outlet installation angles ( β 1 and β 2 ) were taken as control variables, and the total power loss and the minimum NPSHr of the pump were taken as the objective functions. The optimization results were that D 1  = 58 mm and D 2  = 162 mm and β 1  = 17° and β 2  = 31°. The hydraulic efficiency was increased by 1.68%.